Risk of hypotensive reactions is increased when using partial saline replacement for therapeutic plasma exchange. Issue 5 (19th March 2019) - Irani, Mehraboon S.; Toushan, Mazen; Zhang, Liyun; Simpson, Pippa M.; Karafin, Matthew S.
Abstract: Background: Partial normal saline replacement during plasma exchange procedures is a common practice to reduce procedure costs but may increase the risk of adverse events, such as hypotension and citrate reactions. The goal of this study was to compare adverse event rates for the patients that used albumin or albumin/saline as replacement. Study Design and Methods: A retrospective chart review was done of plasma exchange procedures that used all albumin or 80% albumin to 20% normal saline (80/20) as replacement. The procedure type (all albumin vs 80/20), the percent of normal saline used, age, gender, and adverse events during the procedure were recorded. Results: During the study period, 3624 procedures were documented for 401 patients (46% female), age range 0 to 93 years, of which 2453 (67.7%) used 80/20. Overall 91 procedures (2.5%) resulted in a hypotensive event, 26 (0.7%) of which were classified as moderate to severe hypotension, and 40 (1.1%) had reported citrate toxicity. After adjusting for age, gender, and diagnosis using a generalized linear mixed model and backward model selection, results showed that 100% albumin had a significantly lower risk of having hypotension than 80/20 (odds ratio (OR): 0.531 [0.298, 0.946], P = 0.032) and moderate to severe hypotension (odds ratio: 0.140 [95% confidence interval (CI): 0.031, 0.628], P = 0.010). Older age was also predictive of having hypotensive reactions (OR[95%CI] = 1.017, [1.0, 1.034], P = 0.047). Conclusion: Partial saline use as a replacement fluid with albumin during plasma exchange is associated with an increased risk of hypotension. Use of saline as replacement fluid during plasma exchange should be minimized especially in older patients.